Znaczenie "pedagogiki twórczości" w kształceniu pedagogicznym = The significance of the "pedagogy of creativity" in pedagogy education - Magda-Adamowicz, Marzenna (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The interest in academic education system increases in decisive moments as the formation of new social order implicates among other things the search for an adequate model of education. Academic education system has been perceived throughout centuries as an important factor determining social, economic development as it educates specialists with the highest level of qualifications who carry out research creating and spreading new, scientific knowledge. Nowadays, the search for new, more effective and more efficient ways of educating seems crucial.
Keywords: pedagogika twórczości; kształcenie pedagogiczne; kształcenie pedagogiczne studentów; szkolnictwo wyższe